Characterizing the architectural erosion metrics: a systematic mapping study - Baabad, Ahmed; Zulzalil, Hazura; Hassan, Sa’adah; Baharom, Salmi (IEEE, 2022)
Software architecture is crucial in determining success or failure in a variety of software development and design fields. Typically, as a system evolves, software architecture deteriorates. This phenomenon is known as architectural erosion. Several studies have addressed architectural erosion based on different solutions. As a result, the metrics technique is the most prevalent solution for architectural erosion. Nevertheless, a comprehensive description of architectural erosion metrics remains unorganized and scattered. This work aims to conduct a systematic mapping to describe and analyze the architectural erosion metrics to provide an overview of erosion metrics and their current trends. Furthermore, no systematic attempts have been made on architectural erosion metrics. The final samples of this study were specified as a total of 43 included papers. Nearly 100 architectural erosion metrics were found. We proposed nine classifications to address architectural erosion challenges, based on adopted approaches in primary studies. The metrics of architectural erosion provide strong evidence for identifying decay and a rapid enabler factor for the adoption of numerous metrics mechanisms to address architectural erosion. The classification of metrics, which is the first of its kind, benefits researchers and practitioners. However, it can be concluded that various aspects are still ambiguous and require further research on architectural erosion measures